2014
DOI: 10.1155/2014/457050
|View full text |Cite
|
Sign up to set email alerts
|

Study of Agglomeration Characteristics of Hydrate Particles in Oil/Gas Pipelines

Abstract: The force acting on hydrate particles is the critical factor to hydrate slurry stability which serves as fundamental basis for slurry flow assurance. A comprehensive analysis of forces acting on the hydrate particles was executed to determine the major agglomeration forces and separation forces, and comparison of forces reveals that the main agglomeration force is capillary force and the main separation force is shear force. Furthermore, four main influencing factors deciding the hydrate particle agglomeration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…27,33 Insight into the properties and mechanisms of the agglomeration can be provided by the cohesive forces. 34,35 From previous studies, 30,36,37 the capillary liquid bridge (CLB) theory was shown to be the most appropriate model to explain the hydrate particle cohesive force phenomenon. This model describes the liquid bridge present between particles (as shown in Figure 2), which is shown in eq 1:…”
Section: ■ Introductionmentioning
confidence: 99%
“…27,33 Insight into the properties and mechanisms of the agglomeration can be provided by the cohesive forces. 34,35 From previous studies, 30,36,37 the capillary liquid bridge (CLB) theory was shown to be the most appropriate model to explain the hydrate particle cohesive force phenomenon. This model describes the liquid bridge present between particles (as shown in Figure 2), which is shown in eq 1:…”
Section: ■ Introductionmentioning
confidence: 99%
“…Insights into AA mechanisms of action have been obtained by measuring cohesive and adhesive forces. 35,36 After overcoming initial difficulties, the micromechanical force (MMF) apparatus has shown great practical and fundamental potential because it measures directly hydrate interparticle cohesive forces. 23,37,38 For example, Dieker et al 39 and Aman et al 40 investigated the effect of carboxylic acids and crude oils on cyclopentane (CyC5) hydrate particle interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The issue of flow assurance has posed sufficient hazard for the oil and gas industry to employ dedicated flow assurance engineers [1]. forces [56]. The following sections describe the findings from literature relating these forces to agglomeration.…”
Section: Agglomerationmentioning
confidence: 99%
“…Hydrate particles in a suspension of oil and water will agglomerate, and according to many sources, the most accurate representations of agglomeration forces are influenced heavily by the capillary bridge force [1,56,[62][63][64]. Figure 8 presents the proposed capillary bridge geometry linking two nearby particles of radius R 1 and R 2 separated by a distance S; the two fluids of densities ρ 1 and ρ 2 form a surface with interfacial energy γ LL ; the bridge forms an internal contact angle θ p and an embracing angle α with the particle at an immersion depth of d.…”
Section: Capillary Actionmentioning
confidence: 99%
See 1 more Smart Citation